Effect of hardening on toughness captured by stress-based damage nucleation in 6061 aluminum alloy. (November 2019) - Petit, Tom; Besson, Jacques; Ritter, Claire; Colas, Kimberly; Helfen, Lukas; Morgeneyer, Thilo F.
Abstract: A deterioration of fracture toughness, especially of the tearing modulus, with aging time and associated strength increase is observed for aluminum 6061 and reproduced here numerically thanks to a stress-based damage nucleation criterion. A correlative multiscale analysis by scanning electron microscopy, atom probe tomography as well as 3D X-ray laminography shows that coarse particles and the characteristic damage mechanisms do not depend on aging time: the fracture mechanism is typically ductile and transgranular as shown by electron backscatter diffraction analysis of sections of compact tension specimens containing interrupted cracks. Large Mg2 Si inclusions fracture at very low plastic strain, and defects nucleate at large (Fe, Si)-rich inclusions with increasing plastic deformation. Only the hardening nanoprecipitation increases with aging time: aging favors the precipitation of nm-size Mg2 Si precipitates which causes hardening of the matrix so that damage nucleation at coarse inclusions becomes easier - thus leading to a decrease in toughness. Indeed, larger clusters and a substantially higher area fraction of iron based intermetallic particles are found on the fracture surfaces of the longest aging time CT samples compared to the shortest aging time samples. Based on these observations, a Gurson-Tvergaard Needleman type model is proposed to simulate the tearing tests using Finite Elements. It uses damage nucleation kinetics which depend on the maximum principal stress, since a classical strain-based nucleation is not sufficient to reproduce the deterioration of the tearing modulus. Graphical abstract: Image 1